Drug Susceptibility and Replication Capacity of a Rare HIV-1 Subtype C Protease Hinge Region Variant. Issue 5 (July 2019) - Zondagh, Jake; Basson, Adriaan E; Achilonu, Ikechukwu; Morris, Lynn; Dirr, Heini W; Sayed, Yasien
Background: Protease inhibitors form the main component of second-line antiretroviral treatment in South Africa. Despite their efficacy, mutations arising within the HIV-1 gag and protease coding regions contribute to the development of resistance against this class of drug. In this paper we investigate a South African HIV-1 subtype C Gag-protease that contains a hinge region mutation and insertion (N37T↑V). Methods: In vitro single-cycle drug susceptibility and viral replication capacity assays were performed on W1201i, a wild-type reference isolate (MJ4) and a chimeric construct (MJ4GagN37T↑VPR). Additionally, enzyme assays were performed on the N37T↑V protease and a wild-type reference protease. Results: W1201i showed a small (threefold), but significant ( P <0.0001) reduction in drug susceptibility to darunavir compared with MJ4. Substitution of W1201i-Gag with MJ4-Gag resulted in an additional small (twofold), but significant ( P <0.01) reduction in susceptibility to lopinavir and atazanavir. The W1201i pseudovirus had a significantly ( P <0.01) reduced replication capacity (16.4%) compared with the MJ4. However, this was dramatically increased to 164% ( P <0.05) when W1201i-Gag was substituted with MJ4-Gag. Furthermore, the N37T↑V protease displayed reduced catalytic processing compared with the SK154 protease. Conclusions: Collectively, these data suggest that the N37T↑V mutation and insertion increases viral infectivity and decreases drug susceptibility. These variations are classified as secondary mutations, and indirectly impact inhibitor binding, enzyme fitness and enzyme stability. Additionally, polymorphisms arising in Gag can modify the impact of protease with regards to viral replication and susceptibility to protease inhibitors.